Express improvement of acute stroke care accessibility in large regions using a centralized telestroke network. (September 2022) - Barragán-Prieto, Ana; Pérez-Sánchez, Soledad; Moniche, Francisco; Moyano, Roberto Valverde; Delgado, Fernando; Martínez-Sánchez, Patricia; Moya, Miguel; Oropesa, Juan M; Mínguez-Castellanos, Adolfo; Villegas, Inmaculada; Álvarez Soria, María José; Tamayo Toledo, Jose Antonio; et al.
Introduction: Acute ischemic stroke therapy has improved in recent decades, decreasing the rates of disability and death among stroke patients. Unfortunately, all health care systems have geographical disparities in infrastructure for stroke patients. A centralized telestroke network might be a low-cost strategy to reduce differences in terms of geographical barriers, equitable access, and quality monitoring across different hospitals. Aims: We aimed to quantify changes in stroke patients' geographic access to specialized evaluation by neurologists and to intravenous acute stroke reperfusion treatments following the rapid implementation of a centralized telestroke network in the large region of Andalusia (8.5 million inhabitants). Methods: We conducted an observational study using spatial and analytical methods to examine how a centralized telestroke network influences the quality and accessibility of stroke care for a large region. Results: In the pre-implementation period, 5, 005, 477 (59.72% of the Andalusian population) had access to specialized stroke care in less than 30 min. After the 5-month process of implementing the telestroke network, 7, 832, 988 (93.5%) inhabitants had an access time of less than 30 min, bridging the gap in acute stroke care in rural hospitals. Conclusions: A centralized telestroke network may be an efficient tool to reduce the differences in stroke care access and quality monitoring across different hospitals, especially in large regions with low population density.